Partnerska współpraca przedsiębiorstw : aspekty informatyczne - Turek, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Partner enterprises can serve as a fine example of changes taking place in modern economy. They distinguish themselves by adopting a new approach towards competitors, whom they often treat as allies rather than enemies. Mutual coordination of operation and combined potential as well as resources, help to achieve common targets. Learning their characteristics and key factors affecting formation of information technology play a pivotal role in decision making process relating to informatisation of partner enterprises. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 407-417